Evaluation of novice reader diagnostic performance in coronary CT angiography using an advanced cardiac software package - Dankerl, Peter; Hammon, Matthias; Tsymbal, Alexey; Achenbach, Stephan; Uder, Michael; Janka, Rolf Matthias; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2014)
The purpose of this research was to evaluate whether a commercially available advanced cardiac software package for coronary CT angiography (CTA) interpretation may reliably assist inexperienced readers to screen for significant coronary artery stenoses.Coronary CTA data sets of 61 consecutive patients with suspected coronary artery disease were evaluated by three novice readers with no experience in cardiac CT interpretation. In the first 15 patients, the novice readers were trained to use the advanced cardiac software package (includes automatic detection of coronary vessels, curved MPR and VRT reconstructions and a measurement too) knowing the results of an expert read. In the next 46 patients, the novice readers had to state whether there is a significant coronary artery stenosis ([Formula: see text]50 %) and if they are confident with their diagnosis. The results of the novice readers were compared to the expert read.The 46 coronary CTA data sets contained 184 vessels with 15 stenoses in 9 patients. On a per-vessel analysis, novice reader 1/2/3 demonstrated 60 %/100 %/ 93% sensitivity, and 98 %/90 %/86 % specificity. Per patient, the readers diagnosed 36/28/29 cases correctly as free of stenoses, 6/9/8 correctly as having at least one stenosis, missed 3/0/1 cases with a stenosis and overdiagnosed 1/9/8 patients. Cohen's kappa values for the three readers versus the expert were 0.60, 0.61 and 0.54. The three novice readers felt confident in the diagnosis of 36/33/30 patients. In these patients, they missed one significant stenosis, showed a sensitivity of 100 %/100 %/75 % and a specificity of 100 %/92 %/88 %.The evaluated advanced cardiac software package successfully assists novice readers in interpreting coronary CTA data sets especially in ruling out significant coronary artery stenosis.
EVALuna2:11866